New Insights Into Peptide Cannabinoids: Structure, Biosynthesis and Signaling - Riquelme-Sandoval, Agustín; de Sá-Ferreira, Caio O.; Miyakoshi, Leo M.; Hedin-Pereira, Cecilia (Frontiers in Pharmacology, 2020)
Classically, the endocannabinoid system (ECS) consists of endogenous lipids, of which the best known are anandamide (AEA) and 2 arachidonoylglycerol (2-AG), their enzyme machinery for synthesis and degradation and their specific receptors, cannabinoid receptor one (CB1) and cannabinoid receptor two (CB2). However, endocannabinoids also bind to other groups of receptors. Furthermore, another group of lipids are considered to be endocannabinoids, such as the fatty acid ethanolamides, the fatty acid primary amides and the monoacylglycerol related molecules. Recently, it has been shown that the hemopressin peptide family, derived from α and β chains of hemoglobins, is a new family of cannabinoids. Some studies indicate that hemopressin peptides are expressed in the central nervous system and peripheral tissues and act as ligands of these receptors, thus suggesting that they play a physiological role. In this review, we examine new evidence on lipid endocannabinoids, cannabinoid receptors and the modulation of their signaling pathways. We focus our discussion on the current knowledge of the pharmacological effects, the biosynthesis of the peptide cannabinoids and the new insights on the activation and modulation of cannabinoid receptors by these peptides. The novel peptide compounds derived from hemoglobin chains and their non-classical activation of cannabinoid receptors are only starting to be uncovered. It will be exciting to follow the ensuing discoveries, not only in reference to what is already known of the classical lipid endocannabinoids revealing more complex aspects of endocannabinoid system, but also as to its possibilities as a future therapeutic tool.